THE EFFECT OF USING SONG AS A TEACHING TECHNIQUE ON THE LISTENING SKILLS OF THE SEVENTH GRADE STUDENTS IN SMP NEGERI 1 BANJAR - ., Made Ade Krisna Kurniarta; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk menyelidiki apakah ada atau tidak ada efek yang signifikan dari penggunaan song sebagai teknik mengajar dalam kemampuan mendengarkan dari siswa kelas VII di SMP Negeri 1 Banjar. Desain penelitian yang digunakan adalah Post-test Only Control Group Design. Populasi dalam penelitian ini adalah siswa kelas tujuh SMP Negeri 1 Banjar dan penentuan sampel penelitian menggunakan teknik Cluster Random Sampling. Kelas VIIC terpilih sebagai kelas ekperimen dimana tehnik mengajar song digunakan dan kelas VIIF terpilih sebagai kelas kontrol dimana teknik mengajar lama digunakan. Hasil analis data menunjukan siswa di kelas eksperimen medapatkan hasil yang lebih baik daripada siswa di kelas kontrol. Hal ini dibuktikan oleh hasil statistik deskriptif yang menunjukkan nilai rata-rata kelas eksperimen adalah 79,79 sedangkan nilai rata-rata dari kelompok kontrol adalah 77,29. Selain itu, hasil dari uji t-test juga menunjukkan bahwa nilai tob lebih besar dari tcv tersebut. Nilai tob adalah 2.639 sedangkan nilai tcv adalah1.689 (α = 0,05). Ini berarti bahwa terdapat perbedaan kemampuan mendengarkan siswa yang signifikan antara siswa yang diajarkan dengan menggunakan teknik mengajar song dan mereka yang diajarkan dengan menggunakan teknik mengajar lama. Jadi dapat disimpulkan bahwa song sebagai teknik mengajar dapat meningkatkan kemampuan mendengarkan siswa.Kata Kunci : Teknik mengajar song, teknik mengajar biasa, kemampuan mendengarkan siswa This study aimed at investigating whether or not there was a significant effect of using song as a teaching technique on the listening skills of the seventh grade students in SMP Negeri 1 Banjar. The research design used in this study was Post-test Only Control Group Design. The population in this study was the seventh grade students of SMP Negeri 1 Banjar and the sample of study were selected by using Cluster Random Sampling. Class VIIC was assigned as the experimental group which was taught by using song as a teaching technique, and class VIIF as the control group which was taught by using conventional teaching technique. The result of the data analysis showed that students in the experimental group performed better than the students in the control group. It was proven by the result of the descriptive statistics that showed the mean score of the experimental group was 79.79 while the mean score of the control group was 77.29. The result of the t-test also showed that the value of the tob was higher than the tcv. The value of the tob was 2.639, while the value of the tcv was 1.993 (α = 0.05). It means that there was a significant difference of students’ listening skill on the students who were taught using song as a teaching technique and those who were taught by using conventional teaching technique. It was concluded that using song as a teaching technique can improve students’ listening skills.keyword : Song teaching technique, conventional teaching technique, student’s listening skills